2011
DOI: 10.1007/s13157-011-0174-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Water Level Fluctuations in Kettle Holes Using a Time Series Model

Abstract: Kettle holes are widespread in moraine landscapes. Their hydrological properties may be very vulnerable to changes in climatic conditions. To increase our knowledge of how kettle holes function and how they may be affected by climate change requires a model that can be applied to a variety of them regardless of their properties. We used the PIRFICT time series model to simulate the water levels in kettle holes over the last 50 years. For model calibration we applied time series of two-year lengths. We observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
2
17
1
Order By: Relevance
“…Results of the studies of small water bodies on the American prairies (Woo & Rowsell, 1993;Winter & Rosenberry, 1995;Ferone & Devito, 2004;Skalbeck et al, 2009) have suggested that they are connected with groundwater reservoirs. This has also been demonstrated in a number of studies of moraine ponds in Mecklenburg, Germany (Lehsten, 2011).…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Results of the studies of small water bodies on the American prairies (Woo & Rowsell, 1993;Winter & Rosenberry, 1995;Ferone & Devito, 2004;Skalbeck et al, 2009) have suggested that they are connected with groundwater reservoirs. This has also been demonstrated in a number of studies of moraine ponds in Mecklenburg, Germany (Lehsten, 2011).…”
Section: Introductionsupporting
confidence: 54%
“…The presence of ponds situated in endorheic depressions is thought to be determined by the atmospheric exchange of water, i.e. by precipitation and evaporation (Drwal, 1982;Drwal & Lange, 1985;Drwal, 1990;Lehsten et al, 2011). The amount of water stored in the pond depends on the flux of the atmospheric exchange of water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural ponds are ecological features which may exist naturally in depressions or glacial features such as kettle holes [5], or adjacent to flood plains [6]. Natural ponds may be filled by an underground spring or with rainfall, and in this paper they are regarded as 'reference' conditions because they ideally have minimal human disturbance.…”
Section: Natural (Natural Origin) Pondsmentioning
confidence: 99%